2020
DOI: 10.1101/2020.12.07.20245621
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Excess deaths associated with the Iranian COVID-19 epidemic: a province-level analysis

Abstract: BackgroundThe number of publicly reported deaths from COVID-19 may underestimate the true death toll from the epidemic as they rely on provisional data that are often incomplete or omit undocumented deaths from COVID-19. In addition, these reports may be subject to significant under-reporting due to a limited testing capacity of a country to identify suspect cases. This study estimated the number of seasonal excess deaths attributable to the COVID-19 epidemic in 31 provinces of Iran.MethodsWe gathered the nati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Excess mortality has already been used to estimate the COVID-19 impact in different countries, both in academic literature (e.g. Kontis et al, 2020;Alicandro et al, 2020;Ghafari et al, 2020;Woolf et al, 2020a,b;Blangiardo et al, 2020;Kobak, 2021;Modi et al, 2021;Islam et al, 2021;Bradshaw et al, 2021, among many others) and by major media outlets. It has also been used to compare COVID-19 impact to the impact of major influenza pandemics Petersen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Excess mortality has already been used to estimate the COVID-19 impact in different countries, both in academic literature (e.g. Kontis et al, 2020;Alicandro et al, 2020;Ghafari et al, 2020;Woolf et al, 2020a,b;Blangiardo et al, 2020;Kobak, 2021;Modi et al, 2021;Islam et al, 2021;Bradshaw et al, 2021, among many others) and by major media outlets. It has also been used to compare COVID-19 impact to the impact of major influenza pandemics Petersen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancies may be due to differences in the study area and time. The number of COVID-19 related deaths changes in different waves of the pandemic [24,25]. The results of the current study showed that the most frequent comorbidities among older inpatients were hypertension, diabetes, and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 60%
“…One study showed that the traumatic stress of COVID-19 was higher among some Arab countries like Egypt and Iraq compared to other Arab countries (Shuwiekh et al 2020). Furthermore, this negative impact was more severe among Iranian people based on the mortality and morbidity rate (Ghafari, Kadivar & Katzourakis, 2021). However, as previous studies in the field of stress and trauma revealed, there were individual differences among people in terms of the severity of mental health symptoms experienced after exposure to a stressor or potentially traumatic event (Mancini & Bonanno, 2010;Regehr, Hill, & Glancy, 2000;Zeidner & Ben-Zur, 1994).…”
Section: Introductionmentioning
confidence: 90%